The large isoform of Drosophila melanogaster heterochromatin protein 2 plays a critical role in gene silencing and chromosome structure. - Shaffer, C.D.; Cenci, G.; Thompson, B.; Stephens, G.E.; Slawson, E.E.; Adu-Wusu, K.; Gatti, M.; Elgin, S.C.R. (Genetics, 2006)
Drosophila melanogaster heterochromatin protein 2 (HP2) interacts with heterochromatin protein 1 (HP1). In polytene chromosomes, HP2 and HP1 colocalize at the chromocenter, telomeres, and the small fourth chromosome. We show here that HP2 is present in the arms as well as the centromeric regions of mitotic chromosomes. We also demonstrate that Su(var)2-HP2 exhibits a dosage-dependent modification of variegation of a yellow reporter transgene, indicating a structural role in heterochromatin formation. We have isolated and characterized 14 new mutations in the Su(var)2-HP2 gene. Using wm4h, many (but not all) mutant alleles show dominant Su(var) activity. Su(var)2-HP2 mutant larvae show a wide variety of mitotic abnormalities, but not the telomere fusion seen in larvae deficient for HP1. The Su(var)2-HP2 gene codes for two isoforms: HP2-L (approximately 365 kDa) and HP2-S (approximately 175 kDa), lacking exons 5 and 6. In general, mutations that affect only the larger isoform result in more pronounced defects than do mutations common to both isoforms. This suggests that an imbalance between large and small isoforms is particularly deleterious. These results indicate a role for HP2 in the structural organization of chromosomes and in heterochromatin-induced gene silencing and show that the larger isoform plays a critical role in these processes.